2017
DOI: 10.1002/jcp.25601
|View full text |Cite
|
Sign up to set email alerts
|

Early Subchondral Bone Loss at Arthritis Onset Predicted Late Arthritis Severity in a Rat Arthritis Model

Abstract: Synovitis is usually observed before loss of articular function in rheumatoid arthritis (RA). In addition to the synovium and according to the "Inside-Outside" theory, bone compartment is also involved in RA pathogenesis. Then, we investigated time dependent articular bone loss and prediction of early bone loss to late arthritis severity on the rat adjuvant-induced arthritis (AIA) model. Lewis female rats were longitudinally monitored from arthritis induction (day 0), with early (day 10) and late (day 17) step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…So, a robust animal model with high arthritis rate and synchronicity was required to explore the preclinical phase. As we showed previously, the rat AIA model met these requirements 12 . A previous study using the same model reported increased osteoclast activity at the time of arthritis and later 26 .…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…So, a robust animal model with high arthritis rate and synchronicity was required to explore the preclinical phase. As we showed previously, the rat AIA model met these requirements 12 . A previous study using the same model reported increased osteoclast activity at the time of arthritis and later 26 .…”
Section: Discussionsupporting
confidence: 53%
“…Control rats (CTRL group, n = 35) received only mineral oil. Injection was performed under short and light 2% isoflurane anaesthesia to optimize the full deliverance of the dose and obtain a high rate of arthritis induction 12 . The day of arthritis induction was defined as day 0.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five rats per group were sacrificed after 1 month and the others at 8 months. Rat in vivo monitoring,10 periodontitis validation, biochemistry assays and determination,11 microcomputed analysis and bone histology methods12 were described in the supplementary methods section. Non-parametric tests were performed with p values under 0.05 considered as statistically significant.…”
Section: Methodsmentioning
confidence: 99%